Prospective associations between intelligence, working memory capacity, and intrusive memories of a traumatic film: Potential mediating effects of rumination and memory disorganization. (March 2021) - Roxanne Sopp, M.; Streb, Markus; Brueckner, Alexandra H.; Schäfer, Sarah K.; Lass-Hennemann, Johanna; Mecklinger, Axel; Michael, Tanja
Abstract: Background and objectives: Field research indicates that lower intelligence may predispose trauma-exposed individuals towards the development of re-experiencing symptoms. However, this assumption requires further testing in controlled prospective studies. In the current analog study, we tested whether lower fluid intelligence and lower working memory capacity (WMC) independently contribute to intrusion development. Moreover, we investigated potential mediating effects of trauma memory characteristics and trait rumination. Methods: 118 healthy participants completed tests measuring fluid intelligence and WMC. Two days later, they were exposed to a film clip depicting traumatic events (i.e., so-called trauma film). After exposure to the film, intrusions were assessed using a diary and an intrusion triggering task. Results: Our analyses revealed a negative correlation between fluid intelligence and intrusions during the intrusion triggering task. WMC did not correlate with any intrusion measure. Moreover, planned analyses did not yield any mediation effects. Limitations: We used the trauma film paradigm to examine analog posttraumatic stress symptoms. This approach limits the generalizability of our findings with regard to symptom development following real-life traumatic events. Conclusions: Our results show for the first time that higher fluid intelligence is associated with fewer intrusions of a trauma film. This association was evident for laboratory but not for ambulatory intrusions. By demonstrating this association using a prospective experimental design, our study importantly corroborates previous field research. Highlights: Fluid intelligence was prospectively correlated with intrusive memories. Working memory capacity was not correlated with intrusive memories. Further support that lower pretrauma intelligence may increase risk for PTSD.